Unlocking global carbon reduction potential by embracing low-carbon lifestyles - Yuru Guan; Yuli Shan; Ye Hang; Qingyun Nie; Yu Liu; Klaus Hubacek (Nature Communications)
Abstract Low-carbon lifestyles provide demand-side solutions to meet global climate targets, yet the global carbon-saving potential of consumer-led abatement actions remains insufficiently researched. Here, we quantify the greenhouse gas emissions reduction potential of 21 low-carbon expenditures using a global multi-regional input-output model linked with detailed household expenditure data. Targeting households exceeding the global per-capita average required to stay below 2 degrees, our model captures changes in direct energy use, household consumption and upstream intermediate industrial inputs. We find that implementing a combination of low-carbon expenditures among the top 23.7% emitters reduces global carbon footprints by 10.4 gigatons CO2e (i.e., 40.1% of the household consumption-based emissions of the 116 countries analysed in this study or 31.7% of the global total in 2017). Consumption pattern changes related to mobility and services contribute 11.8% and 10.2% of emission reductions. North America shows substantial reduction potential, while some Sub-Saharan African countries present unexpected mitigation possibilities. However, a rebound effect from re-spending income savings from lifestyle changes offsets the expected carbon savings by 6.5% to 45.8% (0.7–4.8 gigatons CO2e).